Rhizobium radiobacter recovered from blood of a pediatric patient with stem cell transplantation: a case report and characterization of antimicrobial susceptibility profile - Steiner, Bruna; Vieira, Fabiane Jamono; Alves, Marcelle Duarte; Perez, Leandro Reus Rodrigues (Clinical and Biomedical Research, 2014)
Rhizobium radiobacter is an uncommon agent of infection and has been associated with indwelling intravascular devices such as catheter in immunocompromised patients. Here, we report a case of R. radiobacter recovered from blood cultures in stem cell transplantation in a pediatric patient and present an extensive characterization of its antimicrobial susceptibility profile. The isolate presented low MICs to many antimicrobial agents, but high MICs to ceftazidime, piperacillin-tazobactam, aztreonam, and fosfomycin.